Maxillary Sinus Lift Using the Lateral Window Technique with Hydroxyapatite and Beta-Tricalcium Phosphate (β-TCP) Graft - Arthur Ferreira, Ribas; Osvaldo Tatsuo, Yamaguto (Journal of Dentistry And Oral Implants, 2025)
This narrative literature review investigates the clinical feasibility of maxillary sinus lift using the lateral window (or traumatic) technique, employing a grafting material composed of hydroxyapatite associated with beta-tricalcium phosphate. The study is based on the premise that bone resorption and sinus pneumatization—common in edentulous posterior maxillae—pose a challenge to achieving primary stability during dental implant placement. Given the limitation imposed by reduced residual bone height, bone-grafting surgical techniques become necessary to enable implant-supported rehabilitation. The objective of this work is to analyze, through a literature review, the efficacy of combining synthetic biomaterials as an alternative to autogenous bone grafts, which are considered the gold standard in implant dentistry. A bibliographic search was conducted in the PubMed and LILACS databases and through the VHL portal, prioritizing articles addressing the biological properties of alloplastic grafts, the indications of the lateral window technique, and the clinical success rates of implants placed in previously grafted areas using such materials. The findings demonstrated that hydroxyapatite associated with beta-tricalcium phosphate exhibits favorable osteoconductive characteristics, such as adequate porosity and gradual resorption, while allowing the formation of viable bone within a clinically acceptable timeframe. The combination of these materials eliminates the need for a second surgical site, reduces morbidity, and maintains treatment predictability. It is concluded that the lateral window technique associated with synthetic biomaterials is a safe and effective alternative for patients with maxillary bone atrophy, capable of promoting suitable bone beds for dental implant placement and stabilization, with lower surgical risk and satisfactory clinical outcomes.
Keywords: Maxillary Sinus Lift; Hydroxyapatite; Tricalcium Phosphate; Bone Graft; Implant Dentistry